A Clinical Study to Evaluate the Efficacy of Lekhan Basti,Chaturbeej Churna and Varunkanchnar Kashay along with Surya Namaskar on Vata Kapha Artava Dusti w.s.r. to Obese PCOS - Sangeeta; ahmed, Liyakat; mod, Neelam; khathuria, Diksha; dixit, Mahesh (International Research Journal of Ayurveda & Yoga, 2023)
Background- Polycystic Ovarian Syndrome (PCOS) is a common endocrinopathy, which is multifactorial and polygenic condition, manifested as anovulation, signs of hyperandrogenism and multiple small ovarian cysts. Polycystic ovarian syndrome is a Medojroga and Santarpanjanyavyadhi. Material and methods -The present pilot study was designed to evaluate the efficacy of Lekhan Basti ,Chaturbeej Churna And Varunkanchnar Kashay Along With Surya Namaskar on obese PCOS. Total 10 patients were enrolled and study shows extremely significant results. The overall result shows maximum improvement in all the assessment parameters. Results - The overall result shows maximum improvement in all the assessment parameters. Conclusion- from these observation we can conclude that ayurvedic drugs are very effective in weight reduction and in relieving the symptoms of obese pcos